Ethephon and Diethyl Aminoethyl Mixture (EDAH) Reduces Maize Lodging and Enhances Overall Productivity in Maize/Peanut Intercropping - Xiaojin Zou; Jiayi Xu; Huasen Xu; Liang Gong; Lizhen Zhang; Ying Wang; Liangshan Feng; Zhanxiang Sun (Agronomy)
The plant growth regulator EDAH, a combination of ethephon and diethyl aminoethyl hexanoate, has been shown to reduce maize lodging and increase crop yield under monoculture systems. However, its effectiveness under intercropping conditions remains uncertain. This study presents findings from a three-year (2020–2022) experiment that investigated the effects of EDAH application on maize and peanut yields, as well as lodging rates, within a maize/peanut intercropping system. The experimental setup included four treatments: sole maize without EDAH, sole peanut without EDAH, intercropped maize and peanut without EDAH, and intercropped maize and peanut with EDAH. Results across the three years revealed that foliar application of EDAH significantly increased maize yield by 13.6% and peanut yield by 28.3%, compared to the non-EDAH treatment in the intercropping system. Moreover, the land-equivalent ratio improved by 13.4%, indicating better land use efficiency. Maize lodging in the intercropping system with EDAH decreased by 48.7%. Additionally, EDAH-treated maize in the intercropping system exhibited a 12.1% reduction in plant height and a 27.7% reduction in ear height compared to untreated maize. The internodes 1–5 of EDAH-treated intercropped maize were 1.93–7.80 cm shorter, while the basal internode diameter increased by 3.30 to 4.90 cm. These morphological changes contributed to improved stalk strength, as evidenced by increases in stalk crush strength, rind penetration strength, and bending strength, which together improved maize lodging resistance. Collectively, these results suggest that the application of EDAH is a promising measure to reduce maize lodging and increase overall crop productivity in maize/peanut intercropping systems.